2010
DOI: 10.1182/blood-2009-03-213215
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden mutation enhances fibrin formation and dissolution in vivo in a human endotoxemia model

Abstract: Disseminated intravascular coagulation in sepsis is associated with microvascular thrombosis and organ dysfunction. It was expected that prothrombotic disposition such as factor V Leiden (FVL) mutation would worsen clinical outcome. Astonishingly, clinical trial and animal experimental data indicate that FVL can be associated with improved survival. This study investigated the effect of FVL on the response to endotoxin of the coagulation and fibrinolytic system in humans. Fourteen healthy male subjects without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Finally, however, in a more subtle model of endotoxin-induced coagulation activation in humans, it was demonstrated that heterozygous carriers of factor V Leiden had a more pronounced increase in markers of thrombin generation and fibrinogen to fibrin conversion. 70 The authors also found an increase in fibrinolytic activity in factor V Leiden-affected individuals, which they attributed to the facilitating role of soluble fibrin for endogenous fibrinolysis.…”
Section: Prothrombotic Mechanisms In Sepsismentioning
confidence: 94%
“…Finally, however, in a more subtle model of endotoxin-induced coagulation activation in humans, it was demonstrated that heterozygous carriers of factor V Leiden had a more pronounced increase in markers of thrombin generation and fibrinogen to fibrin conversion. 70 The authors also found an increase in fibrinolytic activity in factor V Leiden-affected individuals, which they attributed to the facilitating role of soluble fibrin for endogenous fibrinolysis.…”
Section: Prothrombotic Mechanisms In Sepsismentioning
confidence: 94%
“…Methylation at the ELOVL2 locus has been proposed as a measure of again in forensics [98] and the principle appears to be similar for chimpanzees [144]. The plasma kinetics of 13 C-DHA is strongly related to age [145], while EPA is only slightly related to age and AA is not [146,147]. While these fatty acids are not immediate products of ELOVL2, it is tempting to speculate that methylation of this gene with aging plays a role.…”
Section: Why Fads Genotypes Are Important: Translationmentioning
confidence: 99%
“…For instance, increased risk of thrombotic events and recurrence occur in patients with homozygous and compound heterozygous for Factor V Leiden (FVL) and prothrombin G20210A mutations [11,12]. Patients with FVL mutation displayed higher levels of D-dimer and fibrinogen-fibrin degradation products in plasma [13].…”
Section: Introductionmentioning
confidence: 99%
“…There is the observation and suggestion that F V Leiden may confer a survival advantage in patients with severe sepsis. 23,24 Recent studies have contradicted the purported survival advantage. 25,26,27 It remains to be seen if this sepsis survival is substantiated.…”
Section: Discussionmentioning
confidence: 99%